Discovery, SAR study and ADME properties of methyl 4-amino-3-cyano-1-(2-benzyloxyphenyl)-1H-pyrazole-5-carboxylate as an HIV-1 replication inhibitor. Issue 5 (27th April 2020) - Fichez, Jeanne; Soulie, Cathia; Le Corre, Laurent; Sayon, Sophie; Priet, Stéphane; Alvarez, Karine; Delelis, Olivier; Gizzi, Patrick; Prestat, Guillaume; Gravier-Pelletier, Christine; Marcelin, Anne-Geneviève; Calvez, Vincent; et al.
Abstract : Identified as an HIV-1 inhibitor in cellulo, this pyrazole does not belong to the three main classes of anti HIV-drugs, a feature of prime interest in the context of viral resistance. Abstract : Inspired by the antiviral activity of known pyrazole-based HIV inhibitors, we screened our in-house library of pyrazole-based compounds to evaluate their in cellulo activity against HIV-1 replication. Two hits with very similar structures appeared from single and multiple-round infection assays to be non-toxic and active in a dose-dependent manner. Chemical expansion of their series allowed an in-depth and consistent structure–activity-relationship study (SAR) to be built. Further ADME evaluation led to the selection of 4-amino-3-cyano-1-(2-benzyloxyphenyl)-1 H -pyrazole-5-carboxylate with an advantageous pharmacokinetic profile. Finally, examination of its mode of action revealed that this compound does not belong to the three main classes of anti-HIV drugs, a feature of prime interest in the context of viral resistance.